Biological performance and carcass yield of yearling Gumuz sheep under graded level concentrate supplementation in Ethiopia - Alemu Tarekegn; Kifetew Adane; Desalegn Amsalu; Yohanes Wolelaw; Ewnetu Tarekegn (Acta Scientiarum. Animal Sciences, 2023)
An experiment was conducted to investigate the effects of graded levels of concentrate on feed intake, biological performance and carcass characteristics of yearling Gumuz sheep. The sheep were purchased and treated against endo- and ecto- parasites before commencing the study. The experimental animals were offered natural grass hay as a basal ration. The experimental design was a Randomized Complete Block Design (RCBD) with six replications. Treatment feeds were arranged in the same amount of wheat bran but in different levels of sesame seed cake which comprises: 150 g wheat bran + 0 g sesame seed cake DM day-1 (T1), 150 g wheat bran + 250 g sesame seed cake DM day-1 (T2), 150 g wheat bran + 350 g sesame seed cake DM day-1 (T3) and 150 g wheat bran + 450 g sesame seed cake DM day-1 (T4). The experiment was conducted for 90 days after 15 days of adaptation period to the experimental feeds and conditions, which were then followed by carcass evaluation at the end. Sheep in T2 and T4 achieved higher total DM intake (1004.03-1072.57 g day-1) than T1 and T3. Sheep fed on graded-level sesame cake supplements (T2, T3 and T4) recorded significantly higher average daily gain (ADG) than the control (T1) and resulted in higher feed conversion efficiency (FCE). As a result of better slaughter weight (SW) achieved significant hot carcass weight (HCW) was recorded in sheep at T3 and T4. Among the concentrate levels, T2, T3 and T4 were found optimum in improving carcass yield and major meat quality attributes. Sheep supplemented with T3 had the highest net return (26.66 USD) and highest marginal rate of revenue (MRR) (6.53) compared to the other high-level sesame cake-supplemented groups. Thus, it is recommended that the supplementation of hay with high-level sesame cake supplement (T3) is biologically efficient and potentially profitable in the feeding of growing Gumuz sheep.